Study on preparation process parameters and tribological properties of porous PI materials. Issue 2 (18th January 2022) - Yan, Yanhong; Yang, Chengwen; Zhou, Yanfei; Dong, Wenbin; Yan, Pengjuan; Jia, Zhining
Abstract : Purpose: Previously, the effect of pore-forming agents on the properties of pore size and morphology was studied. In this paper, we determine the optimal combination of parameters by tensile strength and perform tribological tests with optimal combination of parameters. Design/methodology/approach: In this paper, porous polyimide (PI) materials were fabricated using vacuum hot molding technology. The orthogonal experiment was designed to test the mechanical properties of porous PI materials with the process parameters and the content of pore-forming agent as the changing factors. The porous PI oil-bearing materials were obtained by vacuum immersion, and tribological test were carried out. Findings: The results showed that porous PI oil-bearing materials are suitable for low-speed and low-load conditions. The actual value of the friction coefficient basically match with the theoretical value of the regression analysis, and the errors of the friction coefficient are within 10% and 3%, respectively, which proves that the method used in the study is feasible for the friction coefficient prediction. Originality/value: In this paper, we have produced a new porous oil-bearing material with good tribological properties. This study can effectively predict the friction coefficient of PI porous material.